Biological Specimen Preparation for Transmission Electron Microscopy. - Glauert, Audrey M. (Princeton University Press, 2014)
This book contains all the necessary information and advice for anyone wishing to obtain electron micrographs showing the most accurate ultrastructural detail in thin sections of any type of biological specimen. The guidelines for the choice of preparative methods are based on an extensive survey of current laboratory practice. For the first time, in a textbook of this kind, the molecular events occurring during fixation and embedding are analysed in detail. The reasons for choosing particular specimen preparation methods are explained and guidance is given on how to modify est.
Keywords: Mounting of microscope specimens.; Transmission electron microscopy -- Technique.; Échantillons microscopiques -- Préparation.; Microscopie électronique à transmission -- Technique.; SCIENCE -- Life Sciences -- Biochemistry.; NATURE -- Reference.; SCIENCE -- Life Sciences -- Biology.; SCIENCE -- Life Sciences -- General.; Mounting of microscope specimens; Transmission electron microscopy -- Technique; Electronic books.